Interpreting measurements of cardiac function using vendor‐independent speckle tracking echocardiography in children: a prospective, blinded comparison with catheter‐derived measurements. Issue 12 (14th October 2016) - Goudar, Suma P.; Baker, G. Hamilton; Chowdhury, Shahryar M.; Reid, Kimberly J.; Shirali, Girish; Scheurer, Mark A.
Abstract : Background: Adult studies demonstrate that echocardiographic measurements of cardiac function using speckle tracking correlate with invasive measurements, but such data in the pediatric population are sparse. Our aim was to compare speckle‐derived measures of cardiac function to measurements routinely obtained by cardiac catheterization in children. Methods: Echocardiograms were performed on the day of cardiac catheterization. Using Tomtec 2D Cardiac Performance Analysis, longitudinal strain (LS), longitudinal strain rate (LSR), early diastolic LSR, and ejection fraction (EF) for the right and left ventricle (RV and LV) were calculated via speckle tracking. Global LS and LSR were calculated for the LV. These results were compared to cardiac index, maximum ventricular dp/dt (max dp/dt), ventricular end‐diastolic pressure (EDP), and pulmonary capillary wedge pressure (PCWP) obtained by fluid‐filled catheters. A blinded observer performed all echo measurements. Results: Fifty studies were performed on 28 patients ages 4 months to 20 years old. Their diagnoses included cardiac transplant (48 studies), repaired AV septal defect (1), and dilated cardiomyopathy (1). RVEDP ranged from 2 to 22 mm Hg (median=6) and PCWP ranged from 6 to 32 mmHg (median 10). LV global LS and LV 2‐chamber LSR by speckle‐tracking negatively correlated with LV max dp/dt (LV global LS R =−.83, P =.001; LV 2‐chamber LSR R =−.69, P =.009). RV LS weakly correlated with max dp/dt ( R =.363, P =.002). Early diastolic strain rate did not correlate with EDP in either ventricle. Conclusion: Speckle‐derived measurements of function in the LV have stronger correlation than the RV to catheter‐derived measures. LV global LS has the strongest correlation with invasive function measures in children.